2012
DOI: 10.7883/yoken.65.198
|View full text |Cite
|
Sign up to set email alerts
|

Serotype, Shiga Toxin (Stx) Type, and Antimicrobial Resistance of Stx-Producing Escherichia coli Isolated from Humans in Shizuoka Prefecture, Japan (2003^|^ndash;2007)

Abstract: SUMMARY:The serotype, Shiga toxin (Stx) type, and antimicrobial resistance patterns of 138 Stxproducing Escherichia coli (STEC) strains isolated from humans between 2003 and 2007 in Shizuoka Prefecture, Japan were characterized. The predominant O serogroups of the STEC isolates were O157, O26, and O111. Antimicrobial susceptibility testing of the STEC isolates showed that 31 of the 138 isolates (22.5z) were resistant to antibiotics. Compared to the results reported in the previous studies, a higher rate of STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…is now estimated to cause more than one million illnesses and 378 deaths annually [10,11]. E. coli toxins are estimated to cause 176,000 illnesses and 20 fatalities a year [12]. Hence, these two pathogens are a major cause of concern and were therefore selected for our study.…”
Section: Discussionmentioning
confidence: 99%
“…is now estimated to cause more than one million illnesses and 378 deaths annually [10,11]. E. coli toxins are estimated to cause 176,000 illnesses and 20 fatalities a year [12]. Hence, these two pathogens are a major cause of concern and were therefore selected for our study.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that mercury resistance transposons carrying CRL transpose onto EHEC virulence plasmids (Venturini et al, 2010; Venturini and Djordjevic, unpublished results) and we believe that such mechanisms are playing an important role in the spread of CRL among important zoonotic pathogens. An appraisal of the literature shows that MDR EHEC isolates displaying resistance to ampicillin, streptomycin, sulfamethoxazole, trimethoprim, and tetracycline are frequently reported (Schroeder et al, 2002; Singh et al, 2005; Cain et al, 2010; Dawes et al, 2010; Li et al, 2011; Hiroi et al, 2012) but the molecular analyses of where the resistance genes are located are lacking. Nonetheless, these observations suggest that mercury resistance transposons play an important (Gastmeier and Vonberg, 2008) role in the assembly and transmission of CRL among EHEC and other Gram negative pathogens (Szczepanowski et al, 2005; Cain et al, 2010; Venturini et al, 2010; Labar et al, 2012).…”
Section: Antibiotic Use In Agriculture and Veterinary Medicinementioning
confidence: 99%
“…Among these, EHEC O26:H11/H − (nonmotile) are the serotypes that are most frequently associated with severe human diseases in Europe (Gerber et al 2002; Tozzi et al 2003; Ethelberg et al 2004; Espié et al 2008; Mellmann et al 2008; Zimmerhackl et al 2010; Käppeli et al 2011; Buvens et al 2012) and the United States (Jelacic et al 2003; Brooks et al 2005; Hedican et al 2009). Furthermore, EHEC O26 has also been increasingly detected in South American (Rivas et al 2006), Asian (Hiroi et al 2012), and Australian (Vally et al 2012) patients, demonstrating the global dissemination of this EHEC serogroup. Moreover, EHEC O26 infections can be comparable with EHEC O157 infections in the severity of the acute HUS and long-term sequelae (Gerber et al 2002; Pollock et al 2011; Zieg et al 2012; Rosales et al 2012).…”
Section: Introductionmentioning
confidence: 99%